Analysis of ASCON Lightweight Authenticated Encryption for UAV Surveillance Communication Security - Vedaniar Zahra Danardini Mulia; Rizal Amrullah (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2026)
The advancement of Unmanned Aerial Vehicle (UAV) technology has brought attention to the necessity of secure communication in intelligence and surveillance missions. UAV systems are susceptible to a number of cybersecurity threats since they depend on wireless communication, including eavesdropping, spoofing, replay attacks, telemetry manipulation, and hijacking. Although traditional cryptography techniques offer robust security, their high computational and energy costs render them unsuitable for the limited capabilities of UAVs. This study employs a comparative literature assessment of papers published between 2021 and 2026 to analyse ASCON lightweight cryptography as a potential solution for secure UAV surveillance communications. Confidentiality, integrity verification, authentication capabilities, and overall computational and energy efficiency against significant threats are important factors evaluated. The results demonstrate how effectively ASCON supports Authenticated Encryption with Associated Data (AEAD), which provides total security for confidentiality, integrity, and authentication while consuming little energy and computing resources. Additionally, ASCON is more resilient to spoofing and replay attacks than other conventional and lightweight cryptographic methods. This study highlights ASCON's capabilities in limited operating conditions and promotes the use of lightweight authenticated encryption algorithms in future UAV cybersecurity frameworks and embedded surveillance systems.